Treatment of symptomatic fibroid disease using uterine fibroid embolisation: An Australian perspective. (20th January 2020) - Clements, Warren; Ang, W. Catarina; Law, Meng; Goh, Gerard S.
Abstract : Uterine leiomyomata (fibroids) are symptomatic in up to 35% of women and treatment can be a costly burden to the individual and society. Options for treatment range from non‐hormonal, hormonal, minimally invasive, to surgery. While symptoms from smaller fibroids may respond to simple treatment, those with larger fibroids or with a large volume of disease require a more definitive option. Surgery (hysterectomy or myomectomy) are both well‐established treatment modalities with good clinical outcomes. Since the 1990s, uterine fibroid embolisation has emerged as a less invasive option for women than for surgical techniques, while level 1 evidence shows that in the short to mid‐term, there is a similar improvement in symptom‐related quality of life outcomes to surgery, but with reduced hospital stay and reduced cost. However, in the longer term there may be a need for further treatment or retreatment in some patients compared with surgery. Since its introduction, uptake of this procedure in Australia has been low relative to surgical options. This manuscript reviews the current literature surrounding treatment, along with the trends in uptake of embolisation by Australian women, places this in context of current guidelines from major societies, and encourages gynaecologists and interventional radiologists to be aware of the advantages and limitations of embolisation.